Heat-conducting silica gel and preparation method thereof

By using the composite technology of silver nanowires and composite thermal fillers in the thermal conductivity gel and adjusting the proportion of silicone oil, the problem of insufficient thermal conductivity of existing thermal conductivity is solved, and a thermal conductivity gel with high thermal conductivity, good flowability and excellent flexibility is prepared to meet the thermal management needs of high-power devices.

CN119684801APending Publication Date: 2025-03-25MODERN TEXTILE TECH INNOVATION CENT (JIANHU LAB) +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411961611.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The thermal conductivity of existing single-component thermal conductivity is generally below 7W/m·K, which cannot meet the needs of artificial intelligence and high-power devices for efficient thermal management.

Method used

The fiber-like thermal filler silver nanowire is used to combine with specific composite thermal fillers to form a tightly packed high thermal conductivity network, and the silicone molecular network structure is adjusted by adjusting the ratio of vinyl silicone oil, side hydrogen silicone oil and end hydrogen silicone oil in the silicone oil mixture.

Benefits of technology

A thermal conductivity gel with a thermal conductivity of between 9 and 11 W/m·K was prepared, which has high flowability, excellent flexibility and low bonding layer thickness, meeting the needs of efficient thermal management.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005217301650000061
    Figure BDA0005217301650000061
Patent Text Reader

Abstract

The invention belongs to the technical field of thermal interface materials, and particularly relates to heat-conducting silica gel and a preparation method thereof. The invention provides heat-conducting gel with high heat conductivity, high fluidity, excellent flexibility and low bonding layer thickness. The heat-conducting gel is prepared from the following raw materials in parts by weight: 80 to 95 parts of spherical heat-conducting filler blend, 0.3 to 2 parts of silver nanowire, 1 to 19 parts of silicone oil mixture, 0.01 to 0.1 part of catalyst, 0.01 to 0.04 part of inhibitor and 0.7 to 2 parts of coupling agent, wherein the spherical heat-conducting filler blend comprises a heat-conducting filler 1 and a heat-conducting filler 2, the heat-conducting filler 1 is a spherical heat-conducting filler with a Karz particle size of 25-75 [mu] m, and the heat-conducting filler 2 is a compound formed by compounding at least five spherical heat-conducting fillers with a median particle size (D50) of 0.5-40 [mu] m. The obtained heat-conducting gel has the advantages of high heat conductivity, high flowability, excellent flexibility and low bonding layer thickness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of thermal interface materials, and in particular relates to a thermally conductive silicone gel and a preparation method thereof. Background Art

[0002] In recent years, the rise of new energy industry and artificial intelligence has significantly accelerated the development of electronic devices towards miniaturization, integration and high power. The heat generated by electronic devices during operation has increased exponentially, causing the operating temperature of the equipment to continue to rise, seriously affecting the reliability, service life and working performance of the equipment. In the process of electronic device processing, it is almost impossible to achieve absolute smoothness between the contact interface between the heat source and the heat sink, and the gap between the two is usually filled with air. The heat transfer capacity of air is very poor, and its thermal conductivity is only about 0.023W / m·K. Thermal interface materials, also known as thermal conductive materials, thermal conductive interface materials or interface thermal conductive materials, can fill the holes and gaps generated when two solid materials contact, and remove the air in the holes or gaps. Thermal interface materials have higher thermal conductivity, which is more conducive to heat conduction, thereby improving heat dissipation. It is a type of material widely used for heat dissipation in electronic packaging and electronic components. At present, there are three main types of thermal conductive silicone grease, thermal conductive pads, and thermal conductive gels on the market.

[0003] Thermal conductive gel is a high-quality polymer-based composite material with vinyl silicone oil and hydrogenated silicone oil as the resin matrix and metal or inorganic ceramics as fillers, which are evenly mixed into glue and then cured in situ to fill the gaps. Since its degree of cross-linking is between that of thermal grease and thermal gasket, it has neither the "pumping out" phenomenon nor oil leakage problems, nor the disadvantage of limited application scenarios, and has received widespread attention from industry and academia.

[0004] In order to prepare high-performance thermally conductive gels, researchers have adopted methods such as compounding of different fillers, design of silicone cross-linking system, and thermally conductive fillers with higher thermal conductivity. Patent application number CN202311712385.X designs a thermally conductive gel compounded with spherical aluminum powder and zinc oxide of different particle sizes; patent application number CN202310481282.0 discloses a method of first preparing a matrix resin by chain extension reaction of vinyl silicone oil and terminal hydrogen silicone oil, and then adding thermally conductive fillers and mixing them evenly to prepare thermally conductive gel; patent application number 202211347346.X discloses the preparation of thermally conductive gel by amino-modified diamond and epoxy-modified metal oxide as thermally conductive fillers, which can reduce interfacial thermal resistance and achieve high thermal conductivity.

[0005] Although many attempts have been made from the perspectives of filler network, interface modification, and molecular design, the thermal conductivity of single-component thermally conductive gels currently on the market is generally below 7W / m·K. With the large-scale application of artificial intelligence and power devices, higher requirements are placed on thermal management materials. Therefore, it is urgent to develop thermally conductive gels with a thermal conductivity of 9W / m·K or even above 10W / m·K and high fluidity, excellent flexibility, and low adhesive layer thickness. Summary of the invention

[0006] In order to solve the deficiencies in the prior art, the present invention adopts fibrous thermal conductive filler silver nanowires with high thermal conductivity and a specific composite thermal conductive filler (the composite thermal conductive filler is composed of a thermal conductive filler with a specific cut-off particle size and at least 5 thermal conductive fillers with a median particle size of 0.5 to 40 μm) as a compound filler to form a tightly packed high thermal conductive network in a silicone oil mixture, thereby preparing a thermal conductive gel with high thermal conductivity, high fluidity, excellent flexibility and low bonding layer thickness; and the present invention can adjust the silicone molecular network structure by controlling the ratio of vinyl silicone oil, side hydrogen silicone oil and end hydrogen silicone oil in the side silicone oil mixture.

[0007] The technical solution of the present invention:

[0008] The first technical problem to be solved by the present invention is to provide a thermally conductive gel having high thermal conductivity, high fluidity, excellent flexibility and low adhesive layer thickness, which comprises the following raw materials in parts by weight:

[0009] 80-95 parts of a spherical thermally conductive filler blend, 0.3-2 parts of silver nanowires, 1-19 parts of a silicone oil mixture, 0.01-0.1 parts of a catalyst, 0.01-0.04 parts of an inhibitor and 0.7-2 parts of a coupling agent; wherein the spherical thermally conductive filler blend comprises a thermally conductive filler 1 and a thermally conductive filler 2, wherein the thermally conductive filler 1 is a spherical thermally conductive filler having a particle size of 25-75 μm, and the thermally conductive filler 2 is a compound of at least 5 or more spherical thermally conductive fillers having a median particle size (D50) of 0.5-40 μm.

[0010] In the present invention, the cut-off treatment refers to the use of screening means to screen the filler, remove the large particle size filler, and control the maximum particle size. Usually, the value D100 when the cumulative particle size distribution percentage reaches 100% is used as the cut-off particle size, that is, the particles with a particle size smaller than it account for 100%. By performing the cut-off treatment on the filler, the filler particle size distribution can be well controlled. When a filler with a concentrated particle size and a narrow distribution is compounded, it can be easier to fill the gap between the fillers, achieve the grading effect of different particle sizes, form a good heat conduction path, and reduce contact thermal resistance. The median particle size (D50) refers to the particle size corresponding to the cumulative particle size distribution percentage of 50%. Particles with a particle size larger than it account for 50%, and particles with a particle size smaller than it also account for 50%.

[0011] Furthermore, the spherical thermally conductive filler is selected from at least one of silicon dioxide, aluminum oxide, aluminum nitride or silicon carbide.

[0012] Furthermore, the length of the silver nanowire is 40 to 75 μm.

[0013] Furthermore, the silicone oil mixture comprises: vinyl silicone oil, side hydrogen-containing silicone oil and terminal hydrogen-containing silicone oil, and the mass ratio thereof is: 50-75 parts of vinyl silicone oil, 10-20 parts of side hydrogen-containing silicone oil, and 5-40 parts of terminal hydrogen-containing silicone oil.

[0014] Furthermore, in the silicone oil mixture, the vinyl content of the vinyl silicone oil is 0.4-1.0wt%; the hydrogen content of the side hydrogen-containing silicone oil is 0.1-0.75wt%; and the hydrogen content of the terminal hydrogen-containing silicone oil is 0.04-0.18wt%.

[0015] Preferably, the catalyst is Karstedt's platinum catalyst or vinylsiloxane-platinum complex.

[0016] Furthermore, the inhibitor is an alkynol inhibitor; preferably at least one of ethynyl cyclohexanol, methyl butynol or 3,7,11-trimethyl dodecyn-3-ol.

[0017] Furthermore, the coupling agent is selected from at least one of: dodecyltrimethoxysilane, dodecylmethyltriethoxysilane, dodecyltrimethoxysilane, dodecylmethyltriethoxysilane, hexadecyltrimethoxysilane or hexadecylmethyltriethoxysilane.

[0018] Furthermore, the thermal conductivity of the thermally conductive gel material is 9 to 11 W / m·K.

[0019] Furthermore, the viscosity of the thermally conductive gel material is 50-200 Pa·s.

[0020] Furthermore, the Young's modulus of the thermally conductive gel material is 0.2-0.7 MPa.

[0021] Furthermore, the elongation at break of the thermally conductive gel material is 150-200%.

[0022] Furthermore, the minimum adhesive layer thickness of the thermally conductive gel material is 80-180 μm.

[0023] The second technical problem to be solved by the present invention is to provide a method for preparing the above-mentioned thermal conductive gel, wherein the preparation method comprises: firstly mixing a silicone oil mixture, a coupling agent, a spherical thermal conductive filler blend and silver nanowires uniformly to prepare a base gel; then adding a catalyst and an inhibitor to the base gel and mixing uniformly to prepare a single-component thermal conductive gel.

[0024] Furthermore, the mixing temperature for preparing the base glue is 100-130°C.

[0025] Furthermore, the mixing temperature for adding the catalyst and the inhibitor into the base rubber and mixing them uniformly is less than 30°C.

[0026] Furthermore, the mixing equipment for preparing the base rubber is selected from a kneader, a high-speed mixer, a homogenizer or a double planetary mixer.

[0027] Furthermore, the mixing device for adding the catalyst and the inhibitor into the base rubber and mixing them uniformly is selected from one of a kneader, a high-speed mixer, a homogenizer or a double planetary mixer.

[0028] Beneficial effects of the present invention:

[0029] The invention adopts fibrous heat-conducting filler silver nanowires with high thermal conductivity, a compound spherical heat-conducting filler with a particle size of 25 to 75 μm and a median particle size of 0.5 to 40 μm, and then performs secondary compounding to form a tightly packed high heat-conducting network. At the same time, the proportion of vinyl silicone oil, side hydrogen silicone oil and end hydrogen silicone oil in the side silicone oil mixture is controlled to adjust the organic silicon molecular network structure, thereby preparing a heat-conducting gel with high thermal conductivity, high fluidity, excellent flexibility and low bonding layer thickness. DETAILED DESCRIPTION

[0030] The present invention prepares a base glue by uniformly mixing a silicone oil mixture, a coupling agent, a specific spherical thermal conductive filler blend and silver nanowires, and then uniformly mixing the catalyst and the inhibitor into the base glue to prepare a single-component thermal conductive silicone gel; and prepares a thermal conductive gel with high thermal conductivity, high fluidity, excellent flexibility and low adhesive layer thickness by secondary compounding the silver nanowires and the compounded spherical thermal conductive filler and adjusting the cross-linked network structure of the organic silicon.

[0031] The specific implementation modes of the present invention are further described below in conjunction with embodiments, but the present invention is not limited to the scope of the embodiments.

[0032] Example 1

[0033] Add 5.15g of vinyl silicone oil with a vinyl content of 0.7wt%, 2.39g of end hydrogen-containing silicone oil with a hydrogen content of 0.10wt%, 0.40g of side hydrogen-containing silicone oil with a hydrogen content of 0.36wt%, 40g of spherical alumina with a particle size of 75μm, 10g of spherical alumina with a median particle size of 0.5μm, 10g of spherical alumina with a median particle size of 1μm, 10g of spherical alumina with a median particle size of 5μm, 10g of 10μm, 10g of 40μm spherical alumina, 1g of silver nanowires with a length of 70μm, and 1g of hexadecyltrimethoxysilane into a vacuum kneader, heat to 100°C and mix for 1h, then heat to 120°C and mix for 1h, finally heat to 130°C, evacuate to a vacuum degree of -0.099MPa, and mix for 2h to make a base glue.

[0034] 99.96 g of the prepared base glue, 0.02 g of Karstedt's platinum catalyst, and 0.02 g of inhibitor ethynyl cyclohexanol were added into a double planetary mixer and mixed at 25° C. for 1 hour to prepare a thermal conductive gel.

[0035] Pour the prepared thermal conductive gel into the mold for curing at a temperature of 125°C, a pressure of 2 MPa, and a time of 2 h; cut the cured samples into suitable shapes and sizes for testing.

[0036] The thermal conductivity, rheological properties, minimum bonding layer thickness and mechanical properties of the obtained gel are shown in Table 1.

[0037] Example 2

[0038] Add 5.51 g of vinyl silicone oil with a vinyl content of 0.9wt%, 1.84 parts of end hydrogen-containing silicone oil with a hydrogen content of 0.10wt%, 1.84 g of side hydrogen-containing silicone oil with a hydrogen content of 0.36wt%, 40 g of spherical aluminum nitride with a cut-off particle size of 45μm, 9.6 g of spherical alumina with a median particle size of 0.5μm, 9.6 g of spherical alumina with a median particle size of 1μm, 9.6 g of 5μm, 9.6 g of 10μm, and 9.6 g of 40μm spherical alumina, 2 g of silver nanoparticles with a length of 40μm, and 0.8 g of coupling agent hexadecyltrimethoxysilane into a vacuum kneader, heat to 100°C and mix for 1h, then heat to 120°C and mix for 1h, finally heat to 130°C, evacuate to a vacuum degree of -0.099MPa, and mix for 2h to make a base rubber.

[0039] 99.98 g of the prepared base glue, 0.01 g of Karstedt's platinum catalyst, and 0.01 g of inhibitor methyl butynol were added into a double planetary mixer and mixed at 25°C for 1 hour to prepare a thermal conductive gel.

[0040] The prepared thermally conductive gel was poured into a mold for curing at a temperature of 125°C, a pressure of 2 MPa, and a curing time of 2 h. The cured samples were cut into suitable shapes and sizes for testing. The thermal conductivity, rheological properties, minimum bonding layer thickness, and mechanical properties of the obtained gel are shown in Table 1.

[0041] Example 3

[0042] 8.86 g of vinyl silicone oil with a vinyl content of 0.43 wt%, 2.53 g of end hydrogen-containing silicone oil with a hydrogen content of 0.05 wt%, 1.27 g of side hydrogen-containing silicone oil with a hydrogen content of 0.36 wt%, 45 g of spherical silicon carbide with a particle size of 35 μm, 2 g of spherical silicon carbide with a median particle size of 0.5 μm, 4 g of spherical silicon carbide with a hydrogen content of 1 μm, 5 g of spherical silicon carbide with a hydrogen content of 2 μm, 8 g of spherical silicon carbide with a median particle size of 5 μm, 10 g of spherical silicon carbide with a hydrogen content of 10 μm, 11 g of spherical silicon carbide with a hydrogen content of 40 μm, 1.5 g of silver nanowires with a length of 40 μm, and 0.8 g of coupling agent hexadecylmethyltriethoxysilane were added into a vacuum kneader, the temperature was raised to 100° C. and mixed for 1 h, then the temperature was raised to 120° C. and mixed for 1 h, and finally the temperature was raised to 130° C. and evacuated to a vacuum degree of -0.099 MPa, and mixed for 2 h to make a base rubber.

[0043] 99.96 g of the prepared base glue, 0.02 g of Karstedt's platinum catalyst, and 0.02 g of inhibitor 3,7,11-trimethyldodecyne-3-ol were added to a double planetary mixer and mixed at 25° C. for 1 hour to prepare a thermal conductive gel.

[0044] The prepared thermally conductive gel was poured into a mold for curing at a temperature of 125°C, a pressure of 2 MPa, and a curing time of 2 h. The cured samples were cut into suitable shapes and sizes for testing. The thermal conductivity, rheological properties, minimum bonding layer thickness, and mechanical properties of the obtained gel are shown in Table 1.

[0045] Comparative Example 1

[0046] Add 5.82g of vinyl silicone oil with a vinyl content of 0.7wt%, 2.69g of end hydrogen-containing silicone oil with a hydrogen content of 0.10wt%, 0.45g of side hydrogen-containing silicone oil with a hydrogen content of 0.36wt%, 40g of spherical alumina with a cut-off particle size of 75μm, 10g of spherical alumina with a median particle size of 0.5μm, 10g of spherical alumina with a median particle size of 1μm, 10g of 5μm, 10g of 10μm, 10g of 40μm spherical alumina, and 1g of hexadecyltrimethoxysilane into a vacuum kneader, heat to 100°C and mix for 1h, then heat to 120°C and mix for 1h, finally heat to 130°C, evacuate to a vacuum degree of -0.099MPa, and mix for 2h to make a base rubber.

[0047] 99.96 g of the prepared base glue, 0.02 g of Karstedt's platinum catalyst, and 0.02 g of inhibitor ethynyl cyclohexanol were added into a double planetary mixer and mixed at 25° C. for 1 hour to prepare a thermal conductive gel.

[0048] The prepared thermal conductive gel was poured into a mold for curing at a temperature of 125°C, a curing pressure of 2 MPa, and a curing time of 2 h; the cured samples were cut into suitable shapes and sizes for testing. The thermal conductivity, rheological properties, minimum bonding layer thickness, and mechanical properties of the gel are shown in Table 1.

[0049] Comparative Example 2

[0050] Add 5.51 g of vinyl silicone oil with a vinyl content of 0.9wt%, 1.84 parts of end hydrogen-containing silicone oil with a hydrogen content of 0.10wt%, 1.84 g of side hydrogen-containing silicone oil with a hydrogen content of 0.36wt%, 40 g of spherical alumina with a cut-off particle size of 120μm, 9.6 g of spherical alumina with a median particle size of 0.5μm, 9.6 g of spherical alumina with a median particle size of 1μm, 9.6 g of spherical alumina with a median particle size of 1μm, 9.6 g of spherical alumina with a median particle size of 5μm, 9.6 g of 10μm, and 9.6 g of 40μm spherical alumina, 2 g of silver nanoparticles with a length of 40μm, and 0.8 g of coupling agent hexadecyltrimethoxysilane into a vacuum kneader, heat to 100°C and mix for 1h, then heat to 120°C and mix for 1h, finally heat to 130°C, evacuate to a vacuum degree of -0.099MPa, and mix for 2h to make a base rubber.

[0051] 99.98 g of the prepared base glue, 0.01 g of Karstedt's platinum catalyst, and 0.01 g of inhibitor methyl butynol were added into a double planetary mixer and mixed at 25°C for 1 hour to prepare a thermal conductive gel.

[0052] The prepared thermal conductive gel was poured into a mold for curing at a temperature of 125°C, a curing pressure of 2 MPa, and a curing time of 2 h; the cured samples were cut into suitable shapes and sizes for testing. The thermal conductivity, rheological properties, minimum bonding layer thickness, and mechanical properties of the gel are shown in Table 1.

[0053] Comparative Example 3

[0054] Add 5.51 g of vinyl silicone oil with a vinyl content of 0.9wt%, 1.84 parts of end hydrogen-containing silicone oil with a hydrogen content of 0.10wt%, 1.84 g of side hydrogen-containing silicone oil with a hydrogen content of 0.36wt%, 88 g of spherical alumina with a particle size of 45μm, 2 g of silver nanoparticles with a length of 40μm, and 0.8 g of coupling agent hexadecyltrimethoxysilane into a vacuum kneader, heat to 100°C and mix for 1h, then heat to 120°C and mix for 1h, finally heat to 130°C, evacuate to a vacuum degree of -0.099MPa, and mix for 2h to make a base rubber.

[0055] 99.98 g of the prepared base glue, 0.01 g of Karstedt's platinum catalyst, and 0.01 g of inhibitor methyl butynol were added into a double planetary mixer and mixed at 25°C for 1 hour to prepare a thermal conductive gel.

[0056] Comparative Example 4 Cross-linking Structure Control

[0057] Add 8.86g of vinyl silicone oil with a vinyl content of 0.43wt%, 3.8g of side hydrogenated silicone oil with a hydrogen content of 0.36wt%, 45g of spherical silicon carbide with a cut-off particle size of 35μm, 2g of spherical silicon carbide with a median particle size of 0.5μm, 4g of spherical silicon carbide with a 1μm, 5g of spherical silicon carbide with a 2μm, 8g of spherical silicon carbide with a 5μm, 10g of spherical silicon carbide with a 10μm, 11g of spherical silicon carbide with a 40μm, 1.5g of silver nanowires with a length of 40μm, and 0.8g of coupling agent hexadecylmethyltriethoxysilane into a vacuum kneader, heat to 100°C and mix for 1h, then heat to 120°C and mix for 1h, finally heat to 130°C, evacuate to a vacuum degree of -0.099MPa, and mix for 2h to make a base rubber.

[0058] 99.96 g of the prepared base glue, 0.02 g of Karstedt's platinum catalyst, and 0.02 g of inhibitor 3,7,11-trimethyldodecyne-3-ol were added to a double planetary mixer and mixed at 25° C. for 1 hour to prepare a thermal conductive gel.

[0059] The prepared thermal conductive gel was poured into a mold for curing at a temperature of 125°C, a curing pressure of 2 MPa, and a curing time of 2 h; the cured samples were cut into suitable shapes and sizes for testing. The thermal conductivity, rheological properties, minimum bonding layer thickness, and mechanical properties of the gel are shown in Table 1.

[0060] The thermal conductivity, rheological properties, minimum bonding layer thickness and mechanical properties of the obtained gel are shown in Table 1.

[0061] Performance Test:

[0062] The thermal conductivity of the sample of the present invention is measured by the transient plane heat source method Hot Disk (according to ISO / CD 22007-2), taking 10-20g of thermal conductive gel and placing it on the fixture, completely wrapping the Hot Disk probe, and reading the thermal conductivity value; further, gradually increase the holding pressure until the thickness value no longer decreases, raise the temperature to 125°C and keep it for 2 hours to fully solidify it, and the thickness value of the sample at this time is the minimum bonding layer thickness. The tensile strength is tested using the universal material testing machine of INSTRON Company of the United States. The test specimen is a dumbbell-shaped specimen with a length of 50mm, a narrow width of 4mm, and a thickness of 2mm, and the tensile rate is 300mm / min.

[0063] Table 1 Performance comparison table of Examples 1-3 of the present invention and Comparative Examples 1-4

[0064]

[0065] From the data in Table 1, it can be seen that the thermal conductivity of Example 1 is 9.2 W / m·K, while the thermal conductivity of Comparative Example 1 is 6.5 W / m·K, indicating that the addition of silver nanowires can significantly improve the thermal conductivity of the system while maintaining fluidity, flexibility and minimum bonding layer thickness; the viscosity of Example 2 is 196 Pa·s, and the minimum bonding layer thickness is 92 μm, while the viscosity of Comparative Example 2 is 287 Pa·s, and the minimum bonding layer thickness is 250 μm, indicating that the particle size of the spherical thermally conductive filler can effectively improve the fluidity of the system and reduce the minimum bonding layer thickness; while the viscosity of Comparative Example 3 is 400 Pa·s, the Young's modulus is 1.65 MPa, and the elongation at break is 52%, indicating that compounding spherical thermally conductive fillers of different particle sizes can improve fluidity and flexibility; the Young's modulus of Example 3 is 0.35 MPa, and the elongation at break is 189%, while the Young's modulus of Comparative Example 4 is 1.79 MPa, and the elongation at break is 43%, indicating that the control of the cross-linked network structure can greatly improve the flexibility of the system. In summary, the present invention proposes a single-component thermally conductive silicone gel with excellent comprehensive performance, and provides a feasible preparation method.

[0066] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A thermally conductive gel, characterized in that: The thermally conductive gel comprises the following raw materials in parts by weight: 80-95 parts of a spherical thermally conductive filler blend, 0.3-2 parts of silver nanowires, 1-19 parts of a silicone oil mixture, 0.01-0.1 parts of a catalyst, 0.01-0.04 parts of an inhibitor and 0.7-2 parts of a coupling agent; wherein the spherical thermally conductive filler blend comprises a thermally conductive filler 1 and a thermally conductive filler 2, wherein the thermally conductive filler 1 is a spherical thermally conductive filler with a breaking particle size of 25-75 μm, and the thermally conductive filler 2 is a compound of at least 5 or more spherical thermally conductive fillers with a median particle size of 0.5-40 μm.

2. A thermally conductive gel according to claim 1, characterized in that: The spherical thermal conductive filler is selected from at least one of silicon dioxide, aluminum oxide, aluminum nitride or silicon carbide.

3. A thermally conductive gel according to claim 1 or 2, characterized in that: The length of the silver nanowire is 40-75 μm.

4. A thermally conductive gel according to any one of claims 1 to 3, characterized in that: The silicone oil mixture comprises: vinyl silicone oil, side hydrogen-containing silicone oil and terminal hydrogen-containing silicone oil, and the mass ratio thereof is: 50-75 parts of vinyl silicone oil, 10-20 parts of side hydrogen-containing silicone oil, and 5-40 parts of terminal hydrogen-containing silicone oil.

5. A thermally conductive gel according to claim 4, characterized in that: In the silicone oil mixture, the vinyl content of the vinyl silicone oil is 0.4-1.0wt%; the hydrogen content of the side hydrogen-containing silicone oil is 0.1-0.75wt%; and the hydrogen content of the terminal hydrogen-containing silicone oil is 0.04-0.18wt%.

6. A thermally conductive gel according to any one of claims 1 to 5, characterized in that: The catalyst is a platinum catalyst or a vinylsiloxane-platinum complex.

7. A thermally conductive gel according to any one of claims 1 to 6, characterized in that: The inhibitor is an alkynol inhibitor; preferably at least one of ethynyl cyclohexanol, methyl butynol or 3,7,11-trimethyl dodecyn-3-ol; Furthermore, the coupling agent is selected from at least one of: dodecyltrimethoxysilane, dodecylmethyltriethoxysilane, dodecyltrimethoxysilane, dodecylmethyltriethoxysilane, hexadecyltrimethoxysilane or hexadecylmethyltriethoxysilane.

8. The thermally conductive gel according to any one of claims 1 to 7, characterized in that: The thermal conductivity of the thermally conductive gel material is 9 to 11 W / m·K; or: The viscosity of the thermally conductive gel material is 50-200 Pa·s; or: The Young's modulus of the thermally conductive gel material is 0.2-0.7 MPa; or: The elongation at break of the thermally conductive gel material is 150-200%; or: The minimum bonding layer thickness of the thermally conductive gel material is 80-180 μm.

9. The method for preparing a thermally conductive gel according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: firstly, a silicone oil mixture, a coupling agent, a spherical heat-conducting filler blend and silver nanowires are uniformly mixed to prepare a base glue; and then a catalyst and an inhibitor are added to the base glue and uniformly mixed to prepare the heat-conducting gel.

10. The method for preparing a thermally conductive gel according to claim 9, characterized in that: The mixing temperature for preparing the base glue is 100-130°C; Furthermore, the mixing temperature for adding the catalyst and the inhibitor into the base rubber and mixing them uniformly is less than 30°C.

Citation Information

Patent Citations

  • Heat-conducting gel as well as preparation method and application thereof

    CN115895269A

  • Heat-conducting silica gel and preparation method thereof

    CN116535863A

  • Heat-conducting gel and preparation method thereof

    CN117844247A